Association of bone mineral density with nine urinary personal care and consumer product chemicals and metabolites: A national-representative, population-based study. (September 2020) - Wang, Ningjian; Wang, Yuying; Zhang, Haojie; Guo, Yuyu; Chen, Chi; Zhang, Wen; Wan, Heng; Han, Junli; Lu, Yingli
Highlights: The association between phenols and bone health was not systematically measured. Nine urinary phenol biomarkers were measured in a US representative sample. Parabens were related to greater bone mineral density in men/premenopausal women. 2, 4-dichlorophenol was associated with lower bone mineral density in men. BPA was positively associated with osteopenia/osteoporosis in postmenopausal women. Abstract: Personal care and consumer products are extensively used and contain various chemicals that are recognized as endocrine disrupting chemicals. Few epidemiological studies measured the associations of these chemicals and metabolites, especially phenols, with bone health. We measured the associations between nine urinary phenol biomarkers and BMD and the subsequent prevalence of osteopenia/osteoporosis. National representative data from US adults aged over 20 years who participated in the National Health and Nutrition Examination Survey from 2005 to 2010 were used. 2, 267 men, 1, 145 premenopausal women and 1, 033 postmenopausal women were included in the final analyses. Bisphenol A, benzophenone-3, triclosan, butylparaben, ethylparaben, methylparaben, propylparaben, 2, 5-dichlorophenol and 2, 4-dichlorophenol were measured by high-performance liquid chromatography-isotope dilution tandem mass spectrometry. Paraben concentrations, especially ethyl-, methyl- and propylparabens, were related to greater BMD in the femoral neck and intertrochanter and lumbar spine in men and premenopausal women. 2, 4-dichlorophenol concentrations was associated with lower BMD and a higher prevalence of osteopenia + osteoporosis in men. Bisphenol A was associated with a higher prevalence of osteopenia + osteoporosis in the lumbar spine in postmenopausal women. Benzophenone-3 tended to be associated with a higher BMD of femur in men and premenopausal women. In conclusion, certain urinary personal care and consumer product chemicals and metabolites were significantly associated with BMD or osteopenia + osteoporosis. These results further indicate that, in future research, determination of the causal relationships and detection of undelying mechanism could be next important directions.